Determination of Intracellular Osmolytes in Cyanobacterial Cells - Xiaoming Tan; Kuo Song; Cuncun Qiao; Xuefeng Lu (Bio-Protocol, 2018)
Most of the cyanobacteria accumulate osmolytes including sucrose, glucosylglycerol, in their cells in response to salt stress. Here we describe a protocol of our laboratory for extraction and quantification of cyanobacterial intracellular sucrose and glucosylglycerol. We have confirmed this protocol was applicable to at least four kinds of cyanobacteria, filamentous cyanobacterium Anabaena sp. PCC 7120, unicellular cyanobacterium Synechocystis sp. PCC 6803, Synechococcus elongatus PCC 7942 and halotolerant unicellular cyanobacterium Synechococcus sp. PCC 7002.